Experimental drought drives divergent succession of soil microbiota - Sihang Deng; Yunfeng Yang; Xue Guo; Mengting Maggie Yuan; Ya Zhang; Linwei Wu; Weiling Shi; Xishu Zhou; Carolyn R. Cornell; Colin T. Bates; Xiaojun A. Liu; Qiuting Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
As droughts become increasingly severe and prolonged worldwide, understanding how belowground biodiversity changes over time under water limitation is critical for assessing ecosystem resilience. However, long-term and continuous observations of soil microbial responses to drought remain rare. Here, using a 6-y experimental drought in a tallgrass prairie ecosystem, we showed that experimental drought reshaped the community compositions of soil bacteria, fungi, and protists, accompanied by progressive declines in microbial diversity and biomass. Analyses of time–decay relationships and paired community differences between drought and ambient conditions revealed increasingly divergent successional trajectories of soil microbiota under drought. Although stochastic processes dominated community assembly overall, their relative importance declined over time, particularly for bacteria in drought-treated soils, suggesting increasingly strong deterministic environmental filtering imposed by drought. In addition, drought reduced microbial network size but increased the complexity and stability of bacterial networks by favoring drought-tolerant taxa. Furthermore, drought-driven shifts in microbial community compositions significantly altered functional genes and associated ecosystem functioning. These findings suggest that microbial communities may become less variable but more vulnerable, and the detrimental effects of biodiversity loss on ecosystems could be more severe in an increasingly drought-prone world.